EVALUASI PENERAPAN MANAJEMEN PERUBAHAN PADA PENGGABUNGAN ORGANISASI PENYELENGGARA PELABUHAN - Ramlan Syah; Harmein Nasution; Yeni Absah (J-MIND (Jurnal Manajemen Indonesia), 2025)
Port-sector reform has value only insofar as it results in measurable improvements in service performance. This study evaluates the application of change management in the merger of Harbormaster and Port Authority functions at one operational unit (UPT), where the intended integration goals have empirically not been consistently achieved. Using a constructivist qualitative approach with a single-case study design, data were collected through 30 semi-structured interviews, non-participant observation, and a review of 68 documents; analysis followed the Miles–Huberman interactive cycle with NVivo-assisted open–axial–selective coding, and validation through triangulation, member checking, and an audit trail. Core findings indicate a misalignment in the management of Ability-Motivation-Opportunity (AMO) improvements across Lewin’s stages: during unfreeze, policy urgency was established but communication remained largely one-way and passive resistance persisted; during change, procedure harmonization via bridge SOPs, competence-based redeployment, and digital quick wins progressed, yet participation was not well structured, competency mismatches persisted, and complaint handling lacked standardization; during refreeze, work began on a unified SOP and cross-agency KPIs, but standardization and cultural internalization were not yet stable. We conclude that the absence of a systematic change architecture and the lack of formal change agents have stalled integration at administrative unification. The study recommends an “integrated change framework” comprising a guiding coalition, finalization of a unified SOP linked to KPI–reward systems, competency certification for critical roles, high-involvement work practices, and a closed-loop feedback cycle to ensure the sustainable institutionalization of new practices.